Extensive heterozygosity and genetic exchange among natural populations of Leishmania species - Eliza V. C. Alves-Ferreira; Mourad Barhoumi; Tiago R. Ferreira; Matthew W. Brown; Petr Volf; Yusr Saadi-BenAoun; Immen Khammari; Ihcen Kherachi; Akila Fathallah Mili; Zoubir Harrat; Ikram Guizani; David L. Sacks; et al. (Proceedings of the National Academy of Sciences, 2026)
Genetic hybridization within the genus Leishmania has been demonstrated experimentally, but the extent to which this occurs naturally among circulating populations remains enigmatic. The current consensus is that natural populations undergo preponderant clonal evolution, presumably expanding by asexual replication. To investigate the extent to which inter- and intraspecific genetic exchange has impacted Leishmania population genetics, a pan-genus multilocus typing method composed of 27 linked and unlinked genetic markers under purifying, neutral, or positive selection was developed and applied against 254 Leishmania isolates assigned to 11 species, the majority (n = 142) of which had been previously speciated using isoenzyme or DNA sequence typing methodologies. Phylogenetic trees and network analyses identified high levels of heterozygosity and allelic diversity across diverse geographic regions, challenging conventional species designations. Notably, approximately 72% of isolates displayed genetic hybridization, both inter- and intraspecific, resulting in hybrids possessing heterozygous sequence blocks from distinct parental ancestries. Whole-genome sequencing analyses performed on 24 isolates validated the hybridization findings. These results underscore a higher degree of outbreeding within the “Old World” Leishmania populations than previously envisaged. Understanding the genetic dynamics and role of hybridization within the population genetics of Leishmania will provide crucial insight for the design of targeted interventions that mitigate the spread of the debilitating tropical diseases caused by these parasites.